Agama Konghucu adalah Agama: Sebuah Analisis Wacana Kritis terhadap Publikasi Komunitas Konghucu di Masa Orde Baru - Christandi, Lemuel (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
This research examines the formation of Agama Konghucu identity during the New Order era, as reflected in Confucian publications (Gentrika and Genta Rohani). Given that identity is relational, the construction process involved identifying the community itself and the perceptions of others, including those of religions and governments. Despite the government's control over the press and media during the New Order, Gentrika and Genta Rohani persistently worked to construct an Agama Konghucu identity. Employing Critical Discourse Analysis, as developed by Fairclough, as the methodology, this article aims to investigate the construction of Agama Konghucu identity discourses in the Confucian community that were published and distributed during the New Order. This thesis uses Bourdieu's perspective on language in power relations, which is integrated into the methodology. Finally, this research concludes that Confucian media play a significant role as an agent and a medium in the construction process by incorporating specific language practices.